Immune counter-evolution: immortalized B cell clones can undergo ex vivo directed evolution to counteract viral escape - Marsman, Casper; Heinen, Jurgen; Clerico Mosina, Vanessa; Maijoor, Kelly; Bakker, Arjen Q.; Koslowski, Michael; Villa, Alessandra; Gullà, Stefano (Frontiers in Immunology, 2025)
IntroductionAmid the persistent threat of future pandemics, the continuous evolution of SARS-CoV-2 exposed critical challenges for vaccine efficacy and therapeutic interventions, highlighting the need for rapid and adaptable approaches to respond to immune escape variants.MethodsHere, we report the use of immortalized B cell libraries from human peripheral blood mononuclear cells (PBMCs) and tonsil tissues to uncover B cell clones exhibiting cross-reactive neutralization against various SARS-CoV-2 variants and perform directed evolution of immortalized B cell clones to produce antibodies with improved binding and neutralization against emerging SARS-CoV-2 variants.ResultsImmortalization of PBMC and tonsil-derived human B cells was achieved through transduction with retroviral vectors encoding apoptosis inhibitors, yielding transduction efficiencies of 67.5% for PBMCs and 50.2% for tonsil-derived cells. Analysis revealed that immortalized B cell libraries produced with this method retain diverse immunoglobulin isotype representations. Through high-throughput functional screening of approximately 40,000 B cells per library, we identified 12 unique clones with neutralization activity for SARS-CoV-2, leading to selection of monoclonal antibodies with robust neutralization activity against Delta and BA.5 variants. We applied our directed evolution approach to libraries generated by ex vivo AID-induced somatic hypermutation (SHM) of immortalized B cell clones to enhance the affinity and cross-reactivity, resulting in improved binding and neutralization potency to escape variants such as EG.5.1 and JN.1. Furthermore, we engineered a bi-paratopic antibody combining KBA2401, a broadly neutralizing antibody binding to highly conserved epitope on Spike-RBD, and KBA2402, a broadly binding non-neutralizing antibody, resulting in enhanced potency against SARS-CoV-2 variant JN.1 and KP.3.DiscussionOur findings illustrate the use of immortalized B cell libraries for development of therapeutics that adapt to viral evolution and highlight the application of ex vivo directed evolution in refining antibody responses against emerging immune escape SARS-CoV-2 variants. The approach here described offers a promising pathway for rapid therapeutic development in the face of evolving viral threats.